2013
DOI: 10.1371/journal.pone.0079389
|View full text |Cite
|
Sign up to set email alerts
|

The Tension at the Top of the Animal Pole Decreases during Meiotic Cell Division

Abstract: Meiotic maturation is essential for the reproduction procedure of many animals. During this process an oocyte produces a large egg cell and tiny polar bodies by highly asymmetric division. In this study, to fully understand the sophisticated spatiotemporal regulation of accurate oocyte meiotic division, we focused on the global and local changes in the tension at the surface of the starfish (Asterina pectinifera) oocyte in relation to the surface actin remodeling. Before the onset of the bulge formation, the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…Imaging oocytes labelled with fluorescent dextran revealed that they are roughly axisymmetric around the AV-axis, thus justifying a 2D approach in which we only image 2D slices containing the AV-axis with transmission light microscopy, which allowed us to simultaneously measure cell shape and hydrodynamic flow. The assumption of rotational symmetry around the AV-axis has been suggested before [25] and is also supported by the observation that the orientation of the SCW is fully determined by the position of the nucleus [21]. Here it is further supported by the observations that both cell shape changes and hydrodynamic flow are highly symmetric in the plane containing the AV-axis.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Imaging oocytes labelled with fluorescent dextran revealed that they are roughly axisymmetric around the AV-axis, thus justifying a 2D approach in which we only image 2D slices containing the AV-axis with transmission light microscopy, which allowed us to simultaneously measure cell shape and hydrodynamic flow. The assumption of rotational symmetry around the AV-axis has been suggested before [25] and is also supported by the observation that the orientation of the SCW is fully determined by the position of the nucleus [21]. Here it is further supported by the observations that both cell shape changes and hydrodynamic flow are highly symmetric in the plane containing the AV-axis.…”
Section: Discussionsupporting
confidence: 76%
“…This is particularly true for starfish, for which it has been suggested early on that the cytoplasmic flow is causal for the extrusion of the polar body following the SCW [4], but quantitative evidence for this suggestion has been missing. Although it has later been demonstrated that polar body formation is not directly affected by forced changes in cytoplasmic flows [23], the notion that the combination of hydrodynamic flow and local cortical weakening drives polar body extrusion is still present in the literature [24, 25]. We recently showed that the polar body is generated even if the SCW is strongly reduced by myosin II inhibition [21], but our earlier study did not address hydrodynamic flows.…”
Section: Introductionmentioning
confidence: 95%
“…However, both Rac and Arp2/3 are required for meiotic divisions in mouse oocytes, through the regulation of cytoplasmic streaming and spindle migration ( Halet and Carroll, 2007 ; Leblanc et al, 2011 ; Sun et al, 2011a ; Chaigne et al, 2013 , 2016 ; Yi et al, 2013 ; Wang et al, 2014 ). Polar body formation during meiotic maturation is thought to occur through a combination of a SCW, a localized protrusion of the cortex induced by the meiotic spindle, and the canonical cytokinetic signaling apparatus ( Maddox et al, 2012 ; Satoh et al, 2013 ; Bischof et al, 2017 ; Klughammer et al, 2018 ). To investigate the potentially opposing roles of Rac in meiotic cytokinesis, Patiria miniata oocytes expressing markers for actin, Rho activity and the Arp2/3 complex were imaged during first meiosis.…”
Section: Resultsmentioning
confidence: 99%
“…To further explore the notion that the spatiotemporal regulation of cytokinesis might involve antagonism between Rac and Rho, we modulated Rac activity during mitotic divisions in early sea urchin embryos and meiotic divisions in sea star oocytes. In contrast to symmetrical divisions, polar body formation exemplifies a highly asymmetric division that involves a (1) surface contraction wave (SCW) that terminates at the site of polar body formation, (2) protrusion of the anaphase spindle and (3) centralspindlin-mediated ring constriction ( Zhang et al, 2008 ; Maddox et al, 2012 ; Satoh et al, 2013 ), and both Rac and Arp2/3 have been directly or indirectly implicated in this process ( Maddox et al, 2012 ). Live cell imaging of sea urchin zygotes revealed that while neither Rac nor Arp2/3 were not required for cell division in the early embryo, expression of activated mutants of Rac disrupted both cytokinesis and normal actin dynamics throughout the embryo.…”
Section: Introductionmentioning
confidence: 99%
“…There are approximately three hundred genera of starfish, which include approximately 1,900 extant species 9 . One species of starfish, Patiria pectinifera , has a remarkably wide distribution in the marine areas of Japan 10 12 . Such phylogenetic and ecological prosperities of the starfish should (or might) depend on the physiological functions of the larvae, which are acquired in the course of evolution and are valuable for the growth of P. pectinifera into adults.…”
Section: Introductionmentioning
confidence: 99%